Responses of bovine chimaeras combining trypanosomosis resistant and susceptible genotypes to experimental infection with Trypanosoma congolense - Naessens, Jan; Leak, S.G.A.; Kennedy, D.J.; Kemp, Stephen J.; Teale, A.J. (Elsevier, 2003)
West African N'Dama cattle have developed a genetic capacity to survive, reproduce and remain productive under trypanosomosis risk. The cellular and molecular bases of this so-called trypanotolerance are not known, but the trait is manifested by the N'Dama's greater capacity to control parasitaemia and anaemia development during an infection. In order to examine the role of the haematopoietic system in trypanotolerance, we have exploited the tendency for the placentas of bovine twin embryos to fuse. Placental fusion in cattle results in bone marrow chimaerism in twins. By comparison with the N'Dama, cattle of the East African Boran breed are relatively susceptible. We evaluated the role of the haemopoietic system in trypanotolerance by comparing the performance of five Chimaeric Boran/N'Dama twin calves with that of singletons of the two breeds. Chimaeric Boran/N'Dama pairs of twins were produced in recipient Boran cows by embryo transfer, and the majority of haemopoietic cells in all twinned individuals were of Boran origin. Thus, N'Dama chimaeras differed from N'Dama singletons in that the bulk of their haemopoietic system was derived from their susceptible Boran twins, while Boran chimaeras differed little from Boran control animals. All cattle became parasitaemic and developed anaemia. The N'Dama chimaeras did not manage their anaemia and white blood cell counts effectively. However, they were able to limit parasitaemia development. These results suggest that trypanotolerance is the result of two mechanisms, one that improves parasite control and is independent of the genetic origin of the haemopoietic tissue, and another that is influenced by haemopoietic tissue genotype and which improves control over anaemia. The capacity to maintain growth during infection was similarly dependent on the genetic origin of the haemopoietic tissue.